2022
DOI: 10.3390/agronomy12112811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Base Fertilizer and Inorganic Topdressing on Alfalfa Productivity and the Soil Bacterial Community in Saline Soil of the Huanghe River Delta in China

Abstract: Alfalfa (Medicago sativa L.) is an important perennial legume forage that is cultivated in saline soil worldwide. This study aimed to clarify the effects of organic base fertilizer and inorganic topdressing on the productivity of alfalfa growing in saline soil. A three-year field study was conducted in which alfalfa was grown in the saline soil of the Huanghe River Delta with a control (no fertilizer) and three treatments: organic base fertilizer (Base), topdressing with urea fertilizer (Top), and combined bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In this study, significant yield differences were observed in all three alfalfa harvests when under different organic fertilizer application rates, which might be related to the slow nutrient release and the persistent nutrient effects of organic fertilizer [23,24]. In addition to nutrients, salt was also an important influencing factor in the alfalfa yield in this study.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, significant yield differences were observed in all three alfalfa harvests when under different organic fertilizer application rates, which might be related to the slow nutrient release and the persistent nutrient effects of organic fertilizer [23,24]. In addition to nutrients, salt was also an important influencing factor in the alfalfa yield in this study.…”
Section: Discussionmentioning
confidence: 54%
“…It is noteworthy that the effect was more pronounced in the first few years, but gradually diminished in the last few years, and this is mostly likely because of the decline of M. sativa as noted above. Therefore, it is suggested that rational topdressing is key to the high yields of M. sativa, and fertilization can also properly delay the M. sativa decline time (Li, 2002;He et al, 2022), especially after planting for more than five years. tended to be higher in the downslope positions (S3, S4, or S3 + S4) than the upslope positions (S1, S2 or S1 + S2) in the pure forests, while there were no differences in TBL in most silvopastoral systems, indicating that M. sativa has a balanced effect on the tree biomass among the slope positions in the silvopastoral systems.…”
Section: Discussionmentioning
confidence: 99%
“…The significant differences in alfalfa yield among the cutting times was consistent with the results of Hakl [37], who reported that 80% of the yield difference could be explained by the year. Furthermore, He et al [22] concluded that organic fertilizer can increase Given the impacts on environmental safety and human health caused by traditional inorganic fertilizers, specific soil microbes are under consideration to replace fertilizers as an ecofriendly approach for sustainable agricultural development and food security [42]. Rath et al [43] showed that the distribution of salt tolerance traits in communities could be quantified by the dose-response relationship between salinity and bacterial growth, which raises the possibility of agricultural utilization of saline soil.…”
Section: Discussionmentioning
confidence: 99%
“…Salinization significantly affects the relative abundance of soil bacteria, such as Firmicutes, which increase the incidence of bacterial wilt in potato [20,21]. A recent experiment on fertilization of saline soil indicated that the bacterial community plays a crucial role in improving the yield of alfalfa [22]. Generally, 10%-40% of the total applied fertilizer is absorbed by plants and the remaining 60%-90% is lost as a result of leaching, denitrification, and volatilization.…”
Section: Introductionmentioning
confidence: 99%